Physical, Flammability and Mechanical Properties of Polymer Eco-Nanocomposites - Alhuthali, Abdullah; Alamri, Hatem; Low, It-Meng (Jim) (Nova Science Publishers Inc, 2012)
When compared to their synthetic counterparts, natural fibres represent an environmentally friendly alternative by virtue of several attractive attributes that include lower density, lower cost, non-toxicity, ease of processing, renewability and recyclability. In addition, the use of natural fibres in polymer matrix composites has the potential to produce materials with higher specific strength and specific modulus due to their low density. In this chapter, epoxy and vinyl-ester resin matrix composites reinforced with recycled cellulose fibre (RCF) have been fabricated and characterised. Nano-composites from both polymers reinforced with different concentration (1%, 5% and 10%) of nano-clay platelets (30B) and halloysite nano-tubes (HNTs) have been synthesized. The mechanical properties, such as flexural strength, impact toughness, fracture toughness and the effect of water absorption on impact toughness were evaluated. Porosity and flammability properties have been investigated. Results indicated that flexural strength decreased for the majority of samples due to the poor dispersion of nano-fillers and the formation of micro-voids within the samples. In contrast, impact toughness and fracture toughness were improved for all reinforced samples. Water absorption resulted in enhanced impact toughness as a result of local plasticization at the crack-tip. Addition of nanoclay increased the porosities but improved the flammability of all nanocomposites. The effects of RCF and nanoclay additions on the physical and mechanical properties have been discussed in terms of the observed microstructures.